Changes in Consumer Behavior Through E-Payment in the Implementation of Green Economy - Ar, Dhita Pratiwi; Lutfi, Anugrah; Akbar, Muhammad; Layli, Nuril; Salam, Karta Negara (Paradoks : Jurnal Ilmu Ekonomi, 2025)
In recent years, there has been a growing awareness of the importance of adopting environmentally sustainable infrastructure. The shift towards a circular economy and the increased use of digital payment methods (e-payment) have emerged as key drivers of sustainable consumer behavior. This study examines the impact of con-sumer behavior changes through the adoption of e-payment systems within the framework of green economy practices. The research was conducted in Makassar, involving a sample of 150 respondents, and analyzed using Structural Equation Modeling (SEM). The results indicate a significant relationship between consumer behavior changes and the increased use of e-payment, which in turn supports the implementation of green economy practices. The findings highlight that e-payment adoption contributes to reduced carbon emissions and the use of non-renewable resources, promoting a more sustainable and efficient economy.